2017
DOI: 10.1007/s10336-017-1520-1
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Whooper Swans do not cause a decline in Eurasian Wigeon via their grazing impact on habitat

Abstract: The Whooper Swan (Cygnus cygnus) is a good example of successful conservation, with rapidly growing numbers in Fennoscandia in recent decades. To the contrary, Eurasian Wigeon (Mareca penelope) shows a strong negative trend in breeding numbers, which raises conservation concerns.Previous research suggests a causal link between recent population trajectories of the two species.Both preferentially breed on wetlands with abundant horsetail (Equisetum spp.), a plant providing food for Whooper Swan and crucial feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…If any such effects occurred, they were probably overridden by local factors, such as wetland trophic status. Moreover, even though large scale population trends may suggest contrasting colonization-extinction dynamics among species, such dynamics may not be realized at the level of the local community 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If any such effects occurred, they were probably overridden by local factors, such as wetland trophic status. Moreover, even though large scale population trends may suggest contrasting colonization-extinction dynamics among species, such dynamics may not be realized at the level of the local community 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the final sample size in the present study was 58 local communities. Waterbird observations were interpreted as pair numbers using species-specific criteria 59 ; as in our earlier study 56 , a species was considered to be present in a community in a given year if at least one breeding pair was observed in either of the two surveys. For further information on waterbird surveys and data, see Supplementary Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…Equisetum fluviatile (Suhonen et al, 2011;Pöysä et al, 2017). The reasons for these changes are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Support for heterospecific attraction has also been found in a community of seven waterbird species breeding in artificial irrigation ponds in south‐eastern Spain, including species pairs such as mallard and little grebe Tachybaptus ruficollis, and mallard and common shelduck Tadorna tadorna (Sebastián‐González et al 2010). Furthermore, Eurasian wigeon Mareca penelope abundance and the overall abundances of three foraging guilds (surface‐feeding ducks, diving ducks and piscivorous ducks) have been found to be positively associated with whooper swan Cygnus cygnus occurrence at breeding lakes in Finland (Pöysä et al 2018, Holopainen et al 2022). Finally, while commensal feeding associations between swans and several duck species (commensals) have been reported from stopover sites during autumn migration (Källander 2005, Gyimesi et al 2012), whooper swans have also been found to behave aggressively towards smaller waterbirds in wintering areas (Wood et al 2020).…”
Section: Introductionmentioning
confidence: 99%